Social norm feedback intervention on reducing antibiotic abuse: a systematic review - Ying-chao ZENG; Lin SHI; Wei-bin LI (Editorial Office of Chinese Journal of Public Health, 2023)
Objective To comprehend the method and effect of social norm feedback (SNF) intervention on reducing antibiotic abuse for offering a reference to implementation of relevant SNF intervention in China. MethodsStudies on SNF intervention on reducing antibiotic abuse published in English from January 2000 through October 2021 were systematically retrieved via searching databases of PubMed, Embase , Web of Science and Scopus and literatures tracing was also conducted for auxiliary retrieval. Results Totally 14 English literatures were included in the analysis. The reported SNF interventions were conducted mainly among primary health care institutions; some of the interventions were conducted in tertiary hospitals, specialized hospitals and in departments of local medical institutions. The unit-specific SNF was ranked by institution, individual doctor or doctor group. The ranking of prescription number was mainly displayed by fuzzy or accurate peer ranking value or mean value of antibiotic prescriptions. For most of the SNF interventions, the information feedbacks were conducted monthly or quarterly and the comparative information among the intervention-covered physicians were disseminated by paper mail, e-mail or locally-developed specific information system. The three most commonly utilized auxiliary packages within the interventions were patient educational materials, clinical practice guidelines and communication strategy. The effects of the interventions were evaluated with the changes in indicators of antibiotic prescription and cost-benefit analysis before and after the interventions, including changes in antibiotic prescription behavior evaluated with the indicators of standardized antibiotic prescription rate, total standardized antibiotic prescription, defined daily dose (DDD), the inappropriate antibiotic prescription rate according to specific diseases, the total cost of prescriptions saved after intervention, the cost of intervention materials and the benefits of patients. ConclusionThe reported SNF interventions on reducing antibiotic abuse were conducted mainly among primary health care institutions and the target population were doctors with higher number of antibiotic prescriptions or inappropriate antibiotic prescriptions. The performance and outcome of the interventions may provide references for reducing antibiotic abuse in China.